2017
DOI: 10.1017/aog.2017.47
|View full text |Cite
|
Sign up to set email alerts
|

A spatio-temporal analysis of trends in Northern Hemisphere snow-dominated area and duration, 1971–2014

Abstract: ABSTRACT. Seasonal snow-cover modulates water and energy budgets across large areas of the Northern Hemisphere. Previous research, based on satellite imagery interpreted and curated by the Rutgers University Snow Laboratory, has identified significant negative and positive trends in annual snow-covered duration and area at hemispheric and continental scales between 1971 and 2014. This study uses the same dataset to generate more detailed descriptions of spatial variations in these trends, maps intraannual vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 72 publications
1
28
0
Order By: Relevance
“…This allowed us to not only detect SD DUR from the time series, but also SD ON and SD OFF . To extend this work further back in time, one could use lower-spatial-resolution Advanced Very High Resolution Radiometer (AVHRR) data (Allchin and Déry, 2017) or investigate in situ measurements (McClung, 2013;Barton, 2017). Our methods could be used anywhere that the MODIS snow cover product is present; however, the definition of the hydrological year, the LOWESS bandwidth, and the NDSI thresholds may need to be optimized.…”
Section: Significance Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This allowed us to not only detect SD DUR from the time series, but also SD ON and SD OFF . To extend this work further back in time, one could use lower-spatial-resolution Advanced Very High Resolution Radiometer (AVHRR) data (Allchin and Déry, 2017) or investigate in situ measurements (McClung, 2013;Barton, 2017). Our methods could be used anywhere that the MODIS snow cover product is present; however, the definition of the hydrological year, the LOWESS bandwidth, and the NDSI thresholds may need to be optimized.…”
Section: Significance Of Resultsmentioning
confidence: 99%
“…BC has undergone significant landscape changes over the last 20 years. These include widespread forest insect outbreaks (e.g., Stahl et al, 2006b), severe wildfire seasons (e.g., Crowley et al, 2019), summer drought (e.g., Barnett et al, 2005), and extensive harvesting of forests (e.g., Hansen et al, 2013). All of these land cover changes have important effects on snow hydrology (Parajka et al, 2012) and may act to either enhance or reduce the observed interannual SD response to both the ONI and PDO.…”
Section: Uncertaintiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The annual transformation of terrestrial physical properties and conditions by seasonal Administration's climate data record of NH snow-cover, compiled and curated by the Rutgers University Snow Laboratory (hereafter the 'NOAA-Rutgers Snow Archive', NRSA), offers the longest period of record of all remotely-sensed environmental datasets (Robinson et al 2012;Estilow et al 2015). It has therefore formed the foundation for a series of SSC-related investigations since the mid-1990s (Robinson et al 1993;Groisman et al 1994;Frei et al 1999;Dye 2002;Rikiishi et al 2004;Déry and Brown 2007;Choi et al 2010;Cohen et al 2012;Liu et al 2012;Hernández-Henríquez et al 2015;Allchin and Déry 2017).…”
Section: Introductionmentioning
confidence: 99%